The New Swiss Glacier Inventory SGI2016: From a Topographical to a Glaciological Dataset - Linsbauer, Andreas; Huss, Matthias; Hodel, Elias; Bauder, Andreas; Fischer, Mauro; Weidmann, Yvo; Bärtschi, Hans; Schmassmann, Emanuel (Frontiers in Earth Science, 2021)
Glaciers in Switzerland are shrinking rapidly in response to ongoing climate change. Repeated glacier inventories are key to monitor such changes at the regional scale. Here we present the new Swiss Glacier Inventory 2016 (SGI2016) that has been acquired based on sub-meter resolution aerial imagery and digital elevation models, bringing together topographical and glaciological approaches and knowledge. We define the process, workflow and required glaciological adaptations to compile a highly detailed inventory based on the digital Swiss Topographic Landscape model. The SGI2016 provides glacier outlines (areas), supraglacial debris cover and ice divides for all Swiss glaciers referring to the years 2013-2018. The SGI2016 maps 1,400 individual glacier entities with a total surface area of 961±22 km2, whereof 11% (104 km2) are debris-covered. It constitutes the so far most detailed cartographic representation of glacier extent in Switzerland. Interpretation in the context of topographic parameters indicates that glaciers with moderate inclination and low median elevation tend to have highest fractions of supraglacial debris. Glacier-specific area changes since 1973 show the largest relative changes for small and low-elevation glaciers. The analysis further indicates a tendency for glaciers with a high share of supraglacial debris to show larger relative area changes. Between 1973 and 2016, an area change rate of –0.6% a-1 is found. Based on operational data sets and the presented methodology, the Swiss glacier inventory will be updated in six-year time intervals, leading to a high consistency in future glacier change assessments.